Does Democracy Still Fall? A Bibliometric Analysis Two Decade 2004-2024 - Henky Fernando; Yuniar Galuh Larasati; Julia Magdalena Wuysang; Putri Rahmah Nur Hakim; Novita Cahyani (Fenomena)
This study aims to explore and evaluate studies that have addressed issues of democratic failure in the last two decades, 2004-2024. In addition to using bibliometric analysis, this study also uses VOSviewer application-based software in exploring and evaluating entity patterns, themes, and developments of studies that focus on discussing democratic failure in the last two decades, 2004-2024. From exploring 1063 total documents, this study found that the United States, the United Kingdom, and the Russian Federation are the most active in publishing studies focusing on democratic failure in Democratization Journal, Journal of Democracy, Political Quarterly, and Third World Quarterly. However, these studies have not been able to intervene and respond to the structural, cultural, and even spiritual challenges that underlie the difficulty of implementing a democratic political system in the era of globalization. This study also recommends the importance of future studies to analyze the factors and implications of the failure of democracy in concept and practice on the welfare of the people in a country.